Analgesia Effect of Enteric Sustained-Release Tetrodotoxin Pellets in the Rat - Bihong Hong (Pharmaceutics, 2020)
Tetrodotoxin (TTX) was identified as a latent neurotoxin that has a significant analgesia effect. It was rapidly absorbed and excreted in rat after intramuscular (i.m.) injection. To maintain the effect, frequent injections were required. The enteric sustained-release TTX pellets with sucrose pellets as a drug carrier was prepared by fluidized bed spray irrigation, coated in sequence with Eudragit NE30D as a sustained-release layer, hydroxypropyl methylcellulose (HPMC) as a barrier layer and Eudragit L30D-55 as an enteric coating. TTX in the pellets could be sustained released for 12 h in dissolution test. In vivo, TTX pellets reached Cmax at 5 h, and t1/2 was 14.52 ± 2.37 h after intragastrically (i.g.) administration in rat. In acetic acid induced writhing test in rat, the pellets at the dosages of 20, 40, 60 and 80 μg·kg−1 produced analgesic effect at about 1.5 h to 9 h and the strongest effect was at about 3 h to 6 h. Simultaneously, the LD50 of the enteric sustained-release TTX pellets was 840.13 μg·kg−1, and the ED50 was about 30 μg·kg−1. Thus, the therapeutic index was about 25. The enteric sustained-release TTX pellets with absolute analgesia effect and greatly enhanced safety was prepared.